(untitled) (Research, Society and Development, 2022)
There is little understanding of the behavior of rural producers, in addition to the lack of empirical evidence on factors that influence the willingness and ability of rural producers to expand their business (CELE, 2020). In this sense, the objective of this study is to evaluate the innovative behavior of family farmers in the State of RS. The innovative behavior scale was used, based on the creation of a partial structural model based on the original scale proposed by Jong & Hartog (2008). From the dimensions of participatory leadership, external contacts and innovative results, a partial structural model was created based on variances (Partial Least Squares Structural Equation Modeling - PLS-SEM) and the model was evaluated through internal consistency, validities convergent and discriminant and structural and predictive model evaluation of the model. The survey included family farmers in the state, in which 174 questionnaires were collected and analyzed using structural equations (Smart-PLS) and the SPSS program (Statistical Package for the Social Sciences), with analysis of the relationships between the three dimensions. As a result, the proposed structural model is effective and supported by the confirmation of the hypotheses and, therefore, can be considered to verify the innovative behavior of family farmers. In this research, it was possible to infer that family farmers have an innovative behavior of moderate to high intensity and are more oriented towards innovative results, and participatory leadership presented the lowest intensity.